A behavioral intervention promoting physical activity in people with subacute spinal cord injury: secondary effects on health, social participation and quality of life. (June 2017) - Nooijen, Carla FJ; Stam, Henk J; Sluis, Tebbe; Valent, Linda; Twisk, Jos; van den Berg-Emons, Rita JG
Objective: To assess, for people with subacute spinal cord injury, if rehabilitation that is reinforced with the addition of a behavioral intervention to promote physical activity leads to a better health, participation and quality of life. Design: Randomized controlled trial. Setting: Rehabilitation centers. Participants: A total of 39 participants analyzed (45 included), with subacute spinal cord injury in inpatient rehabilitation, dependent on a manual wheelchair (33% tetraplegia, 62% motor complete, 150 ±74 days postinjury). Intervention: A behavioral intervention promoting physical activity after discharge, involving 13 individual sessions delivered by a coach trained in motivational interviewing, beginning two months before and ending six months after discharge from inpatient rehabilitation. Main measures: Physical capacity as determined during a maximal exercise test, body mass index, blood pressure, fasting lipid profile, and social participation (IMPACT-S) and quality of life (SF-36) were determined using questionnaires. Measurements were performed two months before discharge, at discharge, and six and 12 months after discharge from inpatient rehabilitation. B represents the between-group difference. Results: Twelve months after discharge, significant intervention effects were found for diastolic blood pressure (B = –11.35 mmHg, 95% CI = –19.98 to −2.71), total cholesterol (B = –0.89 mmol/L, 95% CI = –1.59 to −0.20), low-density lipoprotein cholesterol (B = −0.63 mmol/L, 95% CI = –1.25 to −0.00) and participation (B = 9.91, 95% CI = 3.34 to 16.48). Conclusions: A behavioral intervention promoting physical activity after discharge from inpatient rehabilitation improves social participation and seems to reduce risk factors for cardiovascular disease in people with subacute spinal cord injury.